Exchange Rate Volatility Effects on the German Labour Market: A Survey of Recent Results and Extensions - Herbert S. Buscher; Claudia Mueller (Institute for the Study of Labor (IZA), 1999)
In this paper, a survey on theoretically expected and empirically proved impacts of exchange rate volatility is given. With regard to the West German unemployment, the effects of volatility are empirically analysed using three different volatility measures and four country groups. In autoregressive models, a significant disturbing impact of volatility can be found with annual data as well as with monthly data for the whole period. While this impact does not differ for the three volatility measures, it is, however, less strong when using the monthly data. Differentiating for different subperiods by use of the monthly data, the reported impact is stronger for relatively stable periods and country groups. When isolating the cyclical component of the unemployment rate, it can be demonstrated that the whole reported impact solely affects this component. In a dynamic Okun-type relation, an additional significant impact of volatility, however, cannot be proved for all subperiods.
Keywords: F31; E32; F16; 330; European Monetary Union; exchange rate volatility; Okun?s law; West German labour market; Wechselkurs; Volatilität; Beschäftigungseffekt; Arbeitslosigkeit; Okuns? Law; Konjunktur; Europäische Wirtschafts- und Währungsunion; Schätzung; Deutschland